PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE FORMULATE-SHARE LISTEN-CREATE TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS VIII SMPN 4 V KOTO KAMPUNG DALAM - Tomia, Nurija (Jurnal Edukasi dan Penelitian Matematika, 2023)
Understanding of mathematical concepts is one of the learning objectives that must be mastered by students. However, in reality at SMPN 4 V Koto Kampung Dalam, class VIII students' understanding of the concepts is still not optimal. One effort to increase students' understanding of mathematical concepts is to apply the Formulate Share Listen Create learning model. The purpose of this research is to describe whether students' understanding of concepts who learn with the Formulate Share Listen Create learning model is better than those who use conventional learning models in class VIII SMPN 4 V Koto Kampung Dalam. This type of research is quasi-experimental with a non-equivalent posttest only control group design. The population in this study were class VIII students at SMPN 4 V Koto Kampung Dalam for the 2022/2023 academic year. The instrument used in this research is a concept understanding test in the form of essay questions. Keywords -  Understanding of Mathematical Concepts, Formulate Share Listen Create, direct learning